Development of a Reference Data Set (RDS) for dental age estimation (DAE) and testing of this with a separate Validation Set (VS) in a southern Chinese population - Jayaraman, Jayakumar; Wong, Hai Ming; King, Nigel M.; Roberts, Graham J. (Journal of forensic and legal medicine, 2016)
Many countries have recently experienced a rapid increase in the demand for forensic age estimates of unaccompanied minors. Hong Kong is a major tourist and business center where there has been an increase in the number of people intercepted with false travel documents. An accurate estimation of age is only possible when a dataset for age estimation that has been derived from the corresponding ethnic population. Thus, the aim of this study was to develop and validate a Reference Data Set (RDS) for dental age estimation for southern Chinese. A total of 2306 subjects were selected from the patient archives of a large dental hospital and the chronological age for each subject was recorded. This age was assigned to each specific stage of dental development for each tooth to create a RDS. To validate this RDS, a further 484 subjects were randomly chosen from the patient archives and their dental age was assessed based on the scores from the RDS. Dental age was estimated using meta-analysis command corresponding to random effects statistical model. Chronological age (CA) and Dental Age (DA) were compared using the paired t-test. The overall difference between the chronological and dental age (CA-DA) was 0.05 years (2.6 weeks) for males and 0.03 years (1.6 weeks) for females. The paired t-test indicated that there was no statistically significant difference between the chronological and dental age (p > 0.05). The validated southern Chinese reference dataset based on dental maturation accurately estimated the chronological age. •The first ever Reference Data Set of dental age estimation for southern Chinese.•The method was proved reliable and accurate for 2–19 years old southern Chinese.•Overall differences between chronological and dental ages were less than 2.6 weeks.